Spatial profiles of magnetosheath parameters under different IMF orientations: THEMIS observations - Pi, Gilbert; Němeček, Zdeněk; Šafránková, Jana; Grygorov, Kostiantyn (Frontiers in Astronomy and Space Sciences, 2024)
Modification of the solar wind parameters at the bow shock (BS) and through the magnetosheath (MSH) is essential for the solar wind–magnetosphere interaction chain. The present study uses two approaches to determine the spatial profile of magnetic field strength and plasma parameters and their fluctuations along the Sun-Earth line under different interplanetary magnetic field (IMF) orientations with an emphasis on radial IMF conditions. The first method is based on the superposed epoch analysis of all the complete THEMIS MSH crossings between 2007 and 2010. The second approach uses the distance of the observing spacecraft from the model magnetopause (MP) expressed in units of an MSH thickness for all THEMIS observations. The results of both these analyses are consistent, and their comparison with simulations reveals the following features: 1) the sign of the IMF north-south component has a negligible effect on the spatial profile of the magnetic field strength or plasma parameters as well as on the level of fluctuations; 2) the ion temperature is enhanced for a radial MF and it is nearly isotropic throughout MSH; 3) the fluctuation level of plasma parameters just downstream BS is enhanced under a radial IMF, but it gradually decreases toward MP to a value typical for other IMF orientations; 4) magnetic field fluctuations are enhanced by a factor of 1.7 in the whole magnetosheath when IMF points radially.